Arduino based water level monitoring and control via can bus - Tuan Abu Bakar, Tuan Ismail (2016)
This thesis presents the water level control system that uses Arduino microcontroller to monitor and control the water level via CAN Bus. The current level of water in the tank is monitored and displayed on the liquid crystal display (LCD) and the system able to control the water level to be at the desired level. The desired level of water is obtained by controlling by pumping the water in and out from the the tank. The level is controlled using Arduino Uno that is interfaced with the plant using CAN Bus that provides the communication between the Arduino and LCD display.